La Acción Constitucional de Habeas Corpus, alcances y limitaciones; y, la manipulación de la clase política de esta garantía atenta a la seguridad jurídica y a la lucha contra la corrupción. - Abad Camacho, Sandra Karina (2023)
Currently in our country the use of the Constitutional Action of "Habeas Corpus" has caused great commotion, for persons deprived of liberty with a final sentence, with sentence and persons who are already serving their sentence, causing the President of the Court to express National Justice "a cascade effect". As a result of the various controversies and communications issued by the different authorities of the Country, my subject of the study entitled “The Constitutional Action of Habeas Corpus, scope and limitations; and, the manipulation of the political class of this guarantee threaten Legal Security and the Fight Against Corruption”. The study carried out shows how the Constitutional Action of Habeas Corpus is being denatured by some Justice Administrators, due to the lack of knowledge of the scope and limitations of this constitutional guarantee, likewise, the interference of the political class in the resolutions issued by the Justice Administrators. The interpretation that the judges are giving to this constitutional action exceeds what is established in the norm; and, therefore, the nature that this jurisdictional guarantee has of protecting the right to freedom, physical integrity and other related rights such as life, thus violating the Right that all citizens have to Legal Security and the fight against the corruption that the country faces every day. This determines a doctrinal, comparative law, normative and jurisdictional study of the sentences issued by the Constitutional Court, to propose scope and limitations that should integrate a Regulation for the application of Habeas Corpus by justice operators and lawyers in free exercise of his profession.